Responses of Various of Wheat (Triticum spp.) Cultivars to Water Status - Sakri, Faisal Abdulkadir; Ghafour, Noori Hassan; Amin, Shireen Abdulkarim (Sulaimani Journal for Pure and Applied Sciences, 2005)
This research was conducted to study the response of various wheat cultivars to water status through plant length , flag leaf length, number of tillers per plant, number of leaves per plant, weight of loosed, plant dry weight, protein content in kernel%, and total carbohydrates, Results indicate that the drought periods significantly days for Sham-3-hard(durum) cultivars and signifiecantly decreased for Maxipak and Abu-Greb cultivars at drought period 21 days and Bakrajow at drought period of 7, 14 and 21 days period fo Aras. Water stress periods significantly decreased number of spike per plant, number of seed per spike, number of seed per plant for all cultivars except Bakrajow for number of seed per spike, and also it significantly decreased weight of loosed especially of the two water stress periods 14, and 21 days and plant dry weight for all cultivars except Sham-3-Soft(aestivum). Drought period significantly decreased protien content in kernel% of Sham-3-Hard in all drought periods and Sham-6-soft at 21 days period.
Keywords: Various wheat Triticum aestivam cultivars Maxipak; AbuGreb; and Sham3hard durum also Aras; Bakrajow and Sham6soft aestivum; water drought periods